Persistent boundaries. Partnership patterns among children of immigrants and natives in Sweden. - Mood, Carina; Jonsson, Jan O. (Journal of Ethnic & Migration Studies, 2026)
Integration theories assume that ingroup partnering (endogamy) among individuals of immigrant background declines as their exposure to majority society increases. We examine this for Sweden, a country with a large and diverse immigrant population. We study cohorts born 1986–1998 who either immigrated as children or were born in Sweden, thereby excluding pre-migration partnerships. We analyse both temporal and spatial exposure using population register data (n>1,000,000) covering both marriages and consensual unions. Our findings show high levels of endogamy by origin group, particularly among those with parents from the Middle East and Africa, where endogamy rates at country level range from 40% to 60%. Partnering with someone of majority background is rare, especially among women. The time exposure hypothesis finds some support as endogamy is higher the older a person was upon immigration. Also, for the second generation, endogamy declines with the family's time in Sweden, although it remains high even after many years for several groups. Surprisingly, we find little evidence that spatial segregation drives endogamy. Ingroup partnering persists even with few co-ethnics in the neighbourhood, perhaps due to online meeting opportunities. Cultural attraction and aversion mechanisms appear to be more decisive than the opportunity structure for partnering.